Grammatical Problems in the Discussion Section of Master Theses - Lidya Rona Mentari; Wisma Yunita; Alamsyah Harahap (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2023)
The discussion section is one part of the thesis that describes the findings of research by demonstrating deep knowledge of the findings, interpreting the findings, and emphasizing the contribution to the current knowledge. Additionally, discussion section is also the most challenging part of the thesis. This study aimed to find out the most grammatical problems and the causes of grammatical problems in discussion section of thesis written by English Education postgraduate Program students at University of Bengkulu. This study used a mixed method in analyzing the data. Most of the grammatical problems were investigated quantitatively, while the causes of grammatical problems were studied qualitatively. The corpuses of this study were 30 master theses written by postgraduate English students who have graduated in 2021. The findings showed that the most frequent grammatical problems found in the discussion section of the thesis were incorrect verbs with 65,4% or 121 times of errors, which were dominated by tense confusion and subject-verb agreement. The cause of the grammatical problems found in the discussion section of the thesis was first-language interference. The conclusion of this study provides information about the most frequent grammatical problems and possible causes in the thesis discussion section to increase the writer's awareness about the importance of grammatical writing in the discussion section.